2021
DOI: 10.1038/s41598-021-03321-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of EEG characteristics while solving scientific problems with different mental effort

Abstract: Studying the mental effort in problem-solving is important to the understanding of how the brain allocates cognitive resources to process information. The electroencephalogram is a promising physiological approach to assessing the online mental effort. In this study, we investigate the EEG indicators of mental effort while solving scientific problems. By manipulating the complexity of the scientific problem, the level of mental effort also changes. With the increase of mental effort, theta synchronization in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Although not statistically significant, such results align with the previous studies that used ERD/ERS (e.g. Zhu et al, 2021) and TRP (e.g. Jia et al, 2021) for measuring and comparing cognitive load in design activities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although not statistically significant, such results align with the previous studies that used ERD/ERS (e.g. Zhu et al, 2021) and TRP (e.g. Jia et al, 2021) for measuring and comparing cognitive load in design activities.…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies using the ERD/ERS indicator often observed higher theta ERS and alpha ERD with increasing task complexity and the associated cognitive load (e.g. Zhu et al, 2021). It has been calculated according to the following equation:…”
Section: Eeg-based Cognitive Load Indicatorsmentioning
confidence: 99%
“…First, too few amputees lead to the lack of universality of results and we will increase the number of amputees in future. Second, more evaluations, such as the time stability of the coding in combination with the forgetting curve ( D’Anna et al, 2019 ), control performance of a prosthetic hand ( Luo et al, 2021 ), and the activation of sensory cortex and mental burden through electroencephalogram (EEG) and functional near-infrared spectroscopy (fNIRS) ( Midha et al, 2021 ; Zhu et al, 2021 ), need to be performed and the results need to be verified. Third, we focused on more reasonable experimental paradigms by setting the stimulation time and rest time ( Buma et al, 2007 ; Marion et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such spatial and spectral information has several advantages, as it leaves the forehead, essential for working memory and executive control, free to be used for measuring other interesting mental states, such as mental effort. This will reduce the probability of incurring confounding effects between the measure of the two different mental states also from a spectral point of view, since mental effort is usually measured in the theta band [62].…”
Section: Discussionmentioning
confidence: 99%